Analisis Pengelolaan Persediaan Bahan Baku Dengan Menggunakan Metode EOQ Pada Lewa Bakery - Suliyanti; Afiah, Nur; Nuraisyiah (Bongaya Journal of Research in Accounting (BJRA), 2025)
This study aims to analyze the management of raw material inventory using the Economic Order Quantity method at the Lewa Bakery in Gowa Regency. Data collection was carried out by interview and documentation. Data analysis was carried out using quantitative descriptive methods. The results of this study indicate tha the EOQ method is an effective and optimal approach for companies in managing inventory and controlling raw material inventory costs. With the EOQ method, the company can save costs of Rp5,090,060.00 or around 67.41%, this method recommends an order quantity of 5,258 kg of raw materials with an order frequency of 10 times a year. In addtion, the EOQ method also recommends a safety stock of 372 kg and a reorder point of 772 kg, which serves to prevent the risk of shortages or excess raw materials, so that the smooth production process can be maintained optimally.